Implementasi Kebijakan Tambahan Penghasilan Aparatur Sipil Negara (ASN) di Kabupaten MAPPI - Cathryn Ulahayanaan; Usman Pakasi; Iqbal Miftakhul Mujtahid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the implementation of the Additional Income Allowance policy in Mappi Regency and analyze the supporting and inhibiting aspects of the Additional Income Allowance policy in Mappi Regency. The method used in this study is qualitative with a data collection process through interviews. Data analysis was carried out through three stages, namely Data Display and Conclusion Drawing/Verification, Data Reduction. The results of the study show that in the communication aspect, 3 important aspects in communicating the additional income policy are language selection, media selection, and type of communication. In providing messages related to the contents of the additional income policy, leaders use verbal language that is easily understood by communicants (employees). Based on the research results, this article concludes several important points, namely that the implementation of the additional income policy is running well and cannot be separated from communication using media, both vertically and horizontally, both print and social media. Keywords: Additional Employee Income, Civil Servants, Policy Implementation